Effect of Anxiety About COVID-19 Infection in the Workplace on the Association Between Job Demands and Psychological Distress - Eguchi, Hisashi; Hino, Ayako; Inoue, Akiomi; Tsuji, Mayumi; Tateishi, Seiichiro; Ando, Hajime; Nagata, Tomohisa; Matsuda, Shinya; Fujino, Yoshihisa (Frontiers in Public Health, 2021)
Purpose There is limited information about the association between workplace psychosocial factors and general worker mental health status during the COVID-19 pandemic. In the present study, we examined how anxiety about being infected by COVID-19 in the workplace affected the association between job demands and psychological distress (PD). Method A cross-sectional online survey was conducted in December 2020. The final analyzed sample was 27,036. The dependent variable of PD was assessed using the Kessler Psychological Distress Scale (K6). Job demands were assessed using the Job Content Questionnaire. Feelings of anxiety were assessed by participants' responses to the following question: “Do you feel anxiety about being infected by COVID-19 in the workplace?” We used a two-level regression adjusting for prefectural level: each individual-level variable at level 1 was nested into each prefecture at level 2, stratified by presence of anxiety. Results A total of 50.5% of participants felt anxious about being infected by COVID-19 in the workplace. The interaction between anxiety and job demands was significant. Job demands were positively associated with PD. In the stratified analysis, the associations were stronger among employees who experienced anxiety about COVID-19 infection in the workplace than among those who did not. Conclusion The association between job demands and PD may be strengthened by anxiety about COVID-19 infection in the workplace.